(untitled) (Communications in Mathematical Research, 2021)
This paper deals with the extinction of weak solutions of the initial and boundary value problem for u_t = div((|u|^σ + d_0)|∇u|^p(x)−2∇u). When the exponent belongs to different intervals, the solution has different singularity (vanishing in finite time).